Enhancing Economic Competitiveness: Analysis of Competitive Advantage Strategies for Durian at PT. Silvia Amerta Jaya - Lukman, Riska Salsabila Ramadani; Adam, Rosida P; Bachri, Syamsul; Lamusa, Faruq (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the competitive advantage strategies implemented by PT. Silvia Amerta Jaya in marketing durian fruit and to identify the factors supporting the company's competitive advantage. The durian market offers profitable prospects, particularly for farmers, to enhance competitive advantage strategies and encourage investments in production growth. A descriptive qualitative approach was employed in this research, with data collected through interviews and analyzed using a SWOT framework. The analysis of internal and external strategic factors revealed the following scores: SO (Strength-Opportunity) at 11.46, ST (Strength-Threat) at 11.02, WO (Weakness-Opportunity) at 11.22, and WT (Weakness-Threat) at 7.78. Based on the SWOT analysis diagram, PT. Silvia Amerta Jaya is positioned in Quadrant I, indicating the presence of significant strengths and opportunities that enable the company to achieve a competitive advantage. These findings suggest that PT. Silvia Amerta Jaya has a robust foundation to capitalize on its market opportunities and maintain its strategic positioning.